2012 IEEE/RSJ International Conference on Intelligent Robots and Systems 2012
DOI: 10.1109/iros.2012.6386044
|View full text |Cite
|
Sign up to set email alerts
|

Slope traversability analysis of reconfigurable planetary rovers

Abstract: Abstract-Future planetary rovers are expected to probe over steep sandy slopes, such as crater rims, where wheel slippage can be a critical issue. One solution to this issue is to mount redundant actuators on the locomotion mechanisms of the rovers such that they can actively reconfigurate themselves to adapt to the driven terrain. In this study, we propose a mechanical model of a rover based on a wheel-soil contact model combined with the classical terramechanic theory. The effects of the rover reconfiguratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
(19 reference statements)
1
12
0
1
Order By: Relevance
“…To reduce this slip, To reduce this slip, Prof. Wettergreen suggested that the posture of the robot should be controlled to remain vertical with respect to gravity [7]. In our research group, we confirmed this suggestion empirically using our wheeled mobile robot and proposed a mechanical model of sideslip based on terramechanics theory [8]. It can be intuitively understood that the horizontal contact configuration shown in Fig.…”
Section: A Sideslip Reduction Methodssupporting
confidence: 66%
“…To reduce this slip, To reduce this slip, Prof. Wettergreen suggested that the posture of the robot should be controlled to remain vertical with respect to gravity [7]. In our research group, we confirmed this suggestion empirically using our wheeled mobile robot and proposed a mechanical model of sideslip based on terramechanics theory [8]. It can be intuitively understood that the horizontal contact configuration shown in Fig.…”
Section: A Sideslip Reduction Methodssupporting
confidence: 66%
“…However, terramechanics theory has mainly been applied to wheels that make vertical contact with the soil, and not to a mobility analysis of reconfigurable rovers with wheels that are able to make sidling contact with the soil. To analyze the effects of reconfiguration over sandy terrain, we extended the conventional terramechanics model to an inclined wheel and applied it to the mechanical model of a reconfigurable rover (Inotsume et al., ). This successfully modeled the relationship between the configuration of a rover and its slippage.…”
Section: Introductionmentioning
confidence: 99%
“…Another important limitation in the application of the classical terramechanic model resides in its two‐dimensional representation and the simplification of the wheel geometry. Lateral forces acting on the wheels during certain operations (e.g., steering or slope climbing) are dismissed and, although some authors have extended these models to take into account side forces (Inotsume et al, ; Ishigami et al, ), their effects are often neglected. In addition, planetary robots make use of grousered wheels to facilitate driving over sandy terrains and, recently, flexible metallic wheels are once again becoming the preferred solution (Richter et al, ; Sharma, Tiwary, Kumar, Suresha Kumar, & Keshava Murthy, ).…”
Section: Terramechanics In Mobile Roboticsmentioning
confidence: 99%
“…These types of passive‐rolling, self‐balancing suspensions have been proven to exhibit great off‐road and obstacle surmounting capabilities but their use and analysis have been limited to a quasistatic framework in which the maximum driving speed considered often does not surpass 10 cm/s. As a result, the quasistatic interaction of this type of robots with sandy, unconsolidated terrains has been widely documented (Ding, Gao, Deng, Nagatani, & Yoshida, ; Inotsume, Sutoh, Nagaoka, Nagatani, & Yoshida, ; Ishigami & Yoshida, ; Ishigami, Miwa, Nagatani, & Yoshida, ; Ishigami, Nagatani, Miwa, & Yoshida, ; Lindemann & Voorhees, ; Oikawa, Yoshida, & Carletti, ). To the extent of the authors’ knowledge, published studies on the performance of planetary robots locomotion subsystems under a dynamic regime are still rather scarce.…”
Section: Introductionmentioning
confidence: 99%